Non-invasive Ventilation During Sanitary Aircraft Evacuation in a Patient with Severe Community-acquired Pneumonia - A. V. Shchyogolev; K. S. Vorobyov; V. V. Shustrov; R. Y. Lakhin (Неотложная медицинская помощь, 2019)
We report the experience of sanitary aviation evacuation of a patient with severe respiratory failure on the background of community-acquired pneumonia using mask non-invasive ventilation. The use of this method of ventilation of the lungs made it possible to avoid undesirable consequences arising from the transfer of the patient to artificial ventilation of the lungs and to transport him safely to a specialized medical institution in order to continue treatment. The described method of preparing a patient with respiratory failure before aviation transportation has shown its effectiveness during the flight and may be recommended for use by airmobile crews when carrying out long-distance evacuation